Magnetic mesoporous nanospheres anchored with LyP-1 as an efficient pancreatic cancer probe. (January 2017) - Jiang, Yongjian; Liu, Shaojun; Zhang, Yu; Li, Hengchao; He, Hang; Dai, Juntao; Jiang, Tao; Ji, Weihang; Geng, Daoying; Elzatahry, Ahmed A.; Alghamdi, Abdulaziz; Fu, Deliang; et al.
Abstract: Immobilization of a ligand that selectively interacts with cancer cells to nanomaterials can enhance their diagnostic and therapeutic efficiency. In this study, we firstly demonstrate the high expression of receptor for cyclic nine-amino acid peptide LyP-1 (Cys-Gly-Asn-Lys-Arg-Thr-Arg-Gly-Cys) in both mouse and human pancreatic cancer. Based on these findings, sub-50 nm multifunctional superparamagnetic mesoporous nanospheres with surface modified with LyP-1 are rationally designed. Theses nanospheres have a core of silica-protected magnetite nanoparticle and a shell of FITC-labeled mesoporous silica, and they are able to specifically recognize and conjugate with the pancreatic cancer cell in vitro, as verified by the combined techniques of fluorescent imaging and T2 weight magnetic resonance imaging. After systematic administration, these LyP-1 immobilized nanospheres are found to actively target to mouse orthotopic xenograft of pancreatic cancer, which opens up the door for applications in early probing and diagnosis of pancreatic cancer by the multimodal imaging. Graphical abstract: Sub-50 nm multifunctional superparamagnetic mesoporous nanospheres with surface modified with LyP-1 are rationally designed. Theses nanospheres have a core of silica-protected magnetite nanoparticle and a shell of FITC-labeled mesoporous silica, and they are able to specifically recognize and conjugate with the pancreatic cancer cell in vitro, as verified by the combined techniques of fluorescent imaging and T2 weight magnetic resonance imaging. After systematic administration, these LyP-1 immobilized nanospheres are found to actively target to mouse orthotopic xenograft of pancreatic cancer, which opens up the door for applications in early probing and diagnosis of pancreatic cancer by the multimodal imaging.